(untitled) (Docentes 2.0 Journal, 2024)
Technology has improved educational processes, pedagogical strategies, and digital skills by using technological tools that contribute to the development of school activities, improve teacher performance, and support professional training. The research objective was to identify students’ perceptions about using technological platforms in higher education to explain their contribution to professional training. The characteristics of this research were framed in the positivist paradigm, a quantitative, non-experimental, cross-sectional, descriptive approach. The universe of the study comprised a convenience sample of 118 students. The analysis of results indicates that the student’s perception is positive and contributes to their professional training since more than 70% interact on Google Classroom, Canvas, Blackboard, Zoom, Kahoot, Facebook, Instagram, WhatsApp, YouTube, or TikTok. The results are consistent with previous studies in which participation in the social networks of WhatsApp, YouTube, or TikTok is highlighted. For the above reasons, it is recommended that a diagnosis be made of the digital skills required by teachers in the classroom.